ANALISIS SPASIAL BASE TRANSCEIVER STATION (BTS) DI KOTA SURAKARTA TAHUN 2012 - Prihananto, Muhammad Ario Bayu (Pendidikan Geografi, 2013)
Muh. Ario Bayu P. K5407033. SPATIAL ANALYSIS OF BASE TRANSCEIVER STATION (BTS) IN SURAKARTA 2012.Thesis, Surakarta:Teacher Training and Education Faculty. Sebelas Maret University. The objectives of research are: (1)To know the BTS spatial distribution pattern of Surakarta in 2012, (2) To know the signal?s range of BTS of Surakarta in 2012,(3)To know the characteristic of user mobile cellular phone on Surakarta 2012. The method used is a descriptive method.Population of this research is the all of BTS tower unit in Surakarta.The sampling technique used ofmobile cellular phone user was multistage random sampling obtaining 150 respondents were taken from different operators.The number of the each operator?s correspondents is based on the percentage of the number of BTS. This research is using primary data and secondary data. The interviews and questioners are the primary data since the documentation study for the secondary.The technique of data analysis are map analysis, nearest neighbour analysis and crossed-table analysis. This research conclude: (1)Spatial distribution of BTS tower of Surakarta in 2012 are majority located in Banjarsari, 67 units or 36,41% of the total number of BTS tower influenced by high population, wide area,and some important facilities which located in here. Most of BTS unit in Surakarta located in flat area. Distribution pattern of BTS in Surakarta is close to random with T=0,5989, (2)The signal range of BTS in Surakarta is about 1 kilometer per unit. It?s depicted from the signal range of BTS that available to cover all of Surakarta?s district, although we still can find blankspot area in several places. Considering the BTS distribution in Surakarta that close to each other and more over the existence of different BTS operator in one tower, we cab conclude that the main street and central of Surakarta became the most valuable area of celluler operator (3)The characteristic of the cell phone users in are majority graduated from senior high school with the age 15-24 year sold, income Rp 500.001,00 ? Rp 1.000.000,00 and profession of the cell phone users as private member. Beside those varieties, price of the service is still become the main consideration for people in choosing operator.